Behavioral economics : the basics - Corr, Philip J.; Plagnol, Anke C. (New York: Routledge, 2019)
"This is the first book to provide a rigorous yet accessible overview of behavioral economics, a growing field that attempts to uncover the psychological processes which mediate the economic decisions we make. Acknowledging that people are swayed by biases and emotions, and don't necessarily have access to good memories or perfect numeracy, behavioral economics challenges the assumptions of informed self-interest within mainstream economic theories. Whether used by paternalist governments to shape our behavior or advertisers and marketers to sell more products, its insights are important and far-reaching, and this is the perfect primer for anyone wishing to understand the key principles"--
What is behavioral economics and why is it important? -- The ascent and dissent of economics -- Econ: homo economicus -- Human: more homer (simpson) than homo economicus -- Manners, monkeys and moods -- Nudge: whys, ways and weasels -- Sell! the commercial (and political) world of persuasion.
Includes bibliographical references and index.
Keywords: Economics; Consumer behavior